Partial clinical response to anakinra in severe palmoplantar pustular psoriasis. (1st September 2014) - Tauber, M.; Viguier, M.; Alimova, E.; Petit, A.; Lioté, F.; Smahi, A.; Bachelez, H.
Summary: Background: Palmoplantar pustular psoriasis is a clinical psoriasis variant characterised by a high impact on quality of life and poor response to biologics approved for plaque type psoriasis.The recombinant interleukin‐1 (IL‐1) receptor antagonist anakinra has been recently used for the treatment of isolated refractory cases of generalised pustular psoriasis with contrasted results. Objectives: To report the clinical response in two patients treated with anakinra as salvage therapy in two patients with severe palmoplantar pustular psoriasis refractory to currently available antipsoriatic systemic therapies. Methods: Anakinra was given subcutaneously at the daily dose of 100 mg, and clinical response was evaluated using the palmoplantar psoriasis area and severity index (PPPASI). Results: Only partial and transient responses were observed in both patients, who had to stop anakinra due to lack of efficacy and to side effects. Conclusion: Anakinra appears to provide only partial clinical improvement in refractory palmoplantar pustular psoriasis. Prospective clinical studies on larger populations are warranted to investigate more accurately both efficacy and safety of IL‐1‐inhibiting strategies in pustular psoriasis.